2014
DOI: 10.1164/rccm.201403-0505oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Interleukin-25 Is a Key Mediator in Th2-High, Corticosteroid-Responsive Asthma

Abstract: Rationale: Activation of type 2 cytokine pathways plays a central role in a large subset of subjects with asthma. Th2-high and Th2-low asthma have distinct clinical, pathologic, and molecular phenotypes and respond differently to therapy. The factors that initiate type 2 responses in some subjects with asthma are unknown.Objectives: To determine whether expression of epithelial cytokines IL-25, IL-33, and thymic stromal lymphopoietin are associated with type 2 responses and predict response to inhaled corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 39 publications
3
123
1
Order By: Relevance
“…Exhaled nitric oxide was slightly lower in the older age group, although this small difference is not likely clinically relevant. More recently recognized Th2 biomarkers, such as periostin, DPP4, and interleukins (in both serum and bronchoalveolar lavage) (33,34), may help further delineate if older subjects with asthma have less active Th2-driven inflammation and thus potentially a reduced response to ICS.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaled nitric oxide was slightly lower in the older age group, although this small difference is not likely clinically relevant. More recently recognized Th2 biomarkers, such as periostin, DPP4, and interleukins (in both serum and bronchoalveolar lavage) (33,34), may help further delineate if older subjects with asthma have less active Th2-driven inflammation and thus potentially a reduced response to ICS.…”
Section: Discussionmentioning
confidence: 99%
“…However, others have reported that airway epithelial cells from subjects with asthma express higher than normal levels of IL-25, which can be induced further by rhinovirus infection (12). Still others have found increased systemic levels of IL-25 in subgroups of patients with asthma with T helper type 2 high asthma (14). Further work is needed to elucidate more clearly the role of IL-25 in human asthma, as well as any potential participation by tuft cells, particularly in the lung, where the differentiation of epithelial cells from precursors differs markedly from the relatively linear and short-lived (3-5 d) process that occurs in the intestines (15).…”
Section: Cross-talk Between Epithelial Cells and Type 2 Immune Signalingmentioning
confidence: 99%
“…IL-33 expression by epithelial cells and smooth muscle cells has also been observed in bronchial asthma [13,14]. IL-25 epithelial expression is increased in patients with asthma and it is associated with the Th2 response [15]. …”
Section: Introductionmentioning
confidence: 99%